2017
DOI: 10.1142/s0219265917410109
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Moore Cayley Graphs

Abstract: The degree-diameter problem seeks to find the largest possible number of vertices in a graph having given diameter and given maximum degree. There has been much recent interest in the problem for mixed graphs, where we allow both undirected edges and directed arcs in the graph. For a diameter 2 graph with maximum undirected degree r and directed out-degree z, a straightforward counting argument yields an upper bound M (z, r, 2) = (z + r) 2 + z + 1 for the order of the graph. Apart from the case r = 1, the only… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Apart from the case r = 1, only three Moore digraphs are known, which are also Cayley graphs. Namely, the already mentioned Bosák digraph, and the two digraphs of Jørgensen [14]; see later Theorem 3.2 by Erskine [9]. Some proofs of the non-existence of Cayley Moore digraphs for some order values have been given by López, Pérez-Rosés, and Pujolàs [17], López, Miret, and Fernández [16] , Erskine [9], and Gavrilyuk, Hirasaka, and Kabanov [12].…”
Section: Preliminariesmentioning
confidence: 98%
See 3 more Smart Citations
“…Apart from the case r = 1, only three Moore digraphs are known, which are also Cayley graphs. Namely, the already mentioned Bosák digraph, and the two digraphs of Jørgensen [14]; see later Theorem 3.2 by Erskine [9]. Some proofs of the non-existence of Cayley Moore digraphs for some order values have been given by López, Pérez-Rosés, and Pujolàs [17], López, Miret, and Fernández [16] , Erskine [9], and Gavrilyuk, Hirasaka, and Kabanov [12].…”
Section: Preliminariesmentioning
confidence: 98%
“…The first part of this paper is a brief survey about known Moore (and almost Moore) general mixed graphs that turn out to be Cayley graphs. More information about Cayley Moore mixed graphs can be found in the paper by Erskine [9]. Our main contribution is described in the second part of the paper, where we give new results on the bipartite case.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…By carrying out a computer search for Cayley mixed graphs that meet the Moore bound Jørgensen found two Cayley mixed Moore graphs with undirected degree r = 3, directed out-degree z = 7, diameter k = 2 and order n = 108 [24]. However, it has been shown that there are no further Cayley mixed Moore graphs with diameter two and order ≤ 485 [17,28]. A search using a SAT solver has also completely ruled out the existence of mixed Moore graphs with diameter two and orders 40, 54 or 84 [26].…”
Section: Notationmentioning
confidence: 99%